Pendampingan Pembuatan Nomor Induk Berusaha (NIB) Melalui Online Single Submission (OSS) Guna Pengembangan Ekonomi UMKM di Kelurahan Tlumpu - Rifqi Darmawan; Ignatia Martha Hendrati; Anis Fitria Utami (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The perpetrators of Small and Medium Enterprise in Tlumpu village of Blitar city is growing every year. In this development, The Small and Medium Enterprise needed some permits to get some legality and protection from the goverment. However, the perpetrators of Small and Medium Enterprise still lack knowledge about to create mechanism of Business Identification Number (NIB) via Online Single Submission’s (OSS) web. This community service aims to clear this problem, which aims to introduce, increase knowledge and assist the perpetrators of Small and Medium Enterprise to create Business Identification Number (NIB) via Online Single Submission’s (OSS) web. There are three implementation methods used, namely socialization, training, and mentoring. The implementation of activities includes the delivery of theory, making licences and submitting business legality letters. The result of this activity is, perpetrators of Small and Medium Enterprise in Tlumpu village of Blitar city show increased knowledge about business legality.